An ADAR1 dsRBD3-PKR kinase domain interaction on dsRNA inhibits PKR activation - Sinigaglia, Ketty; Cherian, Anna; Du, Qiupei; Lacovich, Valentina; Vukić, Dragana; Melicherová, Janka; Linhartova, Pavla; Zerad, Lisa; Stejskal, Stanislav; Malik, Radek; Prochazka, Jan; Bondurand, Nadège; et al. (Cell reports, 2024)
Adar null mutant mouse embryos die with aberrant double-stranded RNA (dsRNA)-driven interferon induction, and Adar Mavs double mutants, in which interferon induction is prevented, die soon after birth. Protein kinase R (Pkr) is aberrantly activated in Adar Mavs mouse pup intestines before death, intestinal crypt cells die, and intestinal villi are lost. Adar Mavs Eifak2 (Pkr) triple mutant mice rescue all defects and have long-term survival. Adenosine deaminase acting on RNA 1 (ADAR1) and PKR co-immunoprecipitate from cells, suggesting PKR inhibition by direct interaction. AlphaFold studies on an inhibitory PKR dsRNA binding domain (dsRBD)-kinase domain interaction before dsRNA binding and on an inhibitory ADAR1 dsRBD3-PKR kinase domain interaction on dsRNA provide a testable model of the inhibition. Wild-type or editing-inactive human ADAR1 expressed in A549 cells inhibits activation of endogenous PKR. ADAR1 dsRNA binding is required for, but is not sufficient for, PKR inhibition. Mutating the ADAR1 dsRBD3-PKR contact prevents co-immunoprecipitation, ADAR1 inhibition of PKR activity, and co-localization of ADAR1 and PKR in cells.
Keywords: A549 Cells; Aicardi-Goutieres Syndrome (AGS); Protein Binding; Adar mutant; dsRNA-binding protein; Mavs; dvouvláknová RNA; Mice; RNA-Binding Proteins; Adenosine Deaminase; RNA, Double-Stranded; Protein Domains; Enzyme Activation; ADAR RNA editing; zvířata; Humans; proteiny vázající RNA; innate immune sensors; vazba proteinů; dsRNA; aktivace enzymů; CP: Molecular biology; myši; eIF-2 Kinase; adenosindeaminasa; protein kinase R; buňky A549; proteinové domény; lidé; kinasa eIF-2; Animals